Lung Cancer Stem Cells as a Target for Therapy - Gorelik, Elieser; Lokshin, Anna; Levina, Vera (Anti-Cancer Agents in Medicinal Chemistry, 2010)
Despite significant efforts in diagnosing and treating lung cancer, therapeutic resistance remains a major unresolved clinical and scientific problem. Cancer stem cells (CSCs) are thought to be responsible for the failure of current chemotherapy of lung cancer. The concept of CSCs has radically changed the view of cancer therapy. Today a majority of current treatment modalities target the differentiated cancer cells and avoid the drug resistant cancer-initiating stem cells. This review summarizes our understanding of lung CSCs and their role in metastasis formation and growth of non- small-cells lung cancer (NSCLC). High tumorigenic and metastatic properties of lung CSCs are associated with the efficient cytokine network production and with the specific signaling pathways. This review underlines the experimental evidence indicating that the stem cell factor (SCF) and its receptor c-kit (CD117) play an important role in survival and proliferation of lung CSCs. Thus, molecularly targeting key cytokine network axes of such highly tumorigenic and metastatic CSCs must be considered for improving the current anti-cancer strategy efficacy. Standard chemotherapy in combination with specific axis of cytokine network targeting, such as SCF-c-kit, could eliminate both bulk tumor cells and CSCs, and therefore to be truly curative therapies. This review provides a summary of some of the developments in the field of lung CSCs targeting and highlights aspects which could help in the drug discovery process.
Keywords: Cancer stem cell targeted therapy